The cardiovascular aspect of COVID-19 - Joseph Adu-Amankwaah; Richard Mprah; Adebayo Oluwafemi Adekunle; Marie Louise Ndzie Noah; Gabriel Komla Adzika; Jeremiah Ong’achwa Machuki; Hong Sun (Annals of Medicine, 2021)
AbstractThe coronavirus disease-2019 (COVID-19), an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2(SARS-CoV-2), has hit the world very hard by affecting millions of people across countries hence posing a major health threat on a global scale. This novel virus is thought to enter and cause infection in its host through the attachment of its structural protein known as the S-glycoprotein to angiotensin-converting enzyme 2 (ACE2). Given the rapid spread of COVID-19 with its consequences globally, it is mandatory that health caregivers and researchers across all disciplines abreast themselves with the potential effects that this novel virus may have on their fields and the medical society at large. During the infection, the cardiovascular system is affected by unknown pathomechanistic processes, hence accounting for an increased prevalence of cardiovascular diseases (CVDs) among COVID-19 patients. As cardiovascular researchers, we are more concerned about the cardiovascular aspect of SARS-CoV-2/COVID-19. Hence, this concise review addresses these aspects where CVD as a risk factor of COVID-19, the prevalence of CVDs in COVID-19, and the potential cardiovascular disorders which may evolve owing to COVID-19 are discussed. A better understanding of these issues will be pivotal to improve cardiovascular health during this SARS-CoV-2/COVID-19 pandemic and beyond.